Dimensi Etis Iklan, Studi Kasus Pada Iklan Sampo Anti Dandruff dan Iklan Belanja Online di Media Televisi - Ni Luh Putu Ratna Suandari; Fajri Rahma Pratiwi; Handriyotopo Handriyotopo (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
The ethical dimension related to advertising ethics towards advertisements broadcast on television media often violates the rules. The case study of the Pantene advertisement version of "Anti Drandruf Ads" played by Anggun C. Sasmi and the online shop version of the Shopee advertisement with Korean artist Black Pink were criticized by KPI regarding broadcast hours and their effect on children. The perspective of this research is the ethical dimension by Kevin Johnston and Tanya Robertson, with descriptive qualitative research methods interpretive analysis of advertising criticism. The evaluative finding of advertising art criticism in this study is that the morality of advertising ethics by comparing it with other products orally is still considered reasonable but the advertising dimension is negative. In the case of the Shopee advertisement with the Black Pink artist, it contains elements of sexism that should not be consumed by children.